System to Prevent the Development of Dermatological Diseases Generated by Overexposure to UV Radiation during Childhood using Open Weather Map API and IoT Wearables - Uribe, Rodrigo A. (2024)
Excessive UV exposure during childhood significantly elevates the risk of dermatological issues, such as premature aging and liver spots, compared to exposure during adulthood. Children typically receive a substantially higher UV dose annually compared to adults, with an average of three times the exposure. By the age of 18, a child may have already received a significant portion, ranging from 50% to 80%, of their lifetime solar radiation exposure. During childhood, children are particularly vulnerable to the harmful effects of excessive sun exposure, as this stage of life often entails prolonged periods of direct UV radiation. This dependency on parental decisions regarding sun exposure duration and protective measures underscores a critical issue. Despite the importance of informed decisions, factors such as insufficient understanding of skin types and misconceptions about UV radiation on cloudy days contribute to inadequate prevention measures. To tackle this problem, our project proposes an innovative solution leveraging the Open Weather Map API in conjunction with wearable IoT devices. This system aims to provide real-time updates on UV radiation levels, empowering parents with valuable information to make more informed choices regarding their children's sun protection. Additionally, personalized reminders and advice tailored to the current weather conditions could be integrated into the system.